DEVELOPMENT OF SPORTS VOLUNTEERING IN MODERN RUSSIA - Myagkova S.N. ,; Zhiyar M.V. ,; Titova G.S. ,; Kachulina N.N. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify the main vectors for the development of sports volunteering in modern Russia. Results and conclusions. It is noted that one of the important directions for the development of the volunteer movement is the development of infrastructure that provides support for volunteering. To do this, volunteer centers are being created in schools, higher education organizations and professional educational institutions, regional resource centers, corporate volunteering centers, as well as “silver volunteering” centers for older people. To date, sports volunteering is being formed as a separate social institution in the all-Russian volunteer movement, as an element in organizing sports events, promoting a healthy lifestyle of the population The idea of sports volunteering is reflected in the national and federal projects of our state. Based on the results of the analysis, practical recommendations and proposals for the development of sports volunteerism are given.